Stigmatized campaign practices and the gendered dynamics of electoral viability - Borges Martins da Silva, M; Gatto, MAC (SAGE Publications, 2021)
What happens when a traditional source of political capital becomes a health hazard? Stigmatized electoral practices, such as vote buying, are a double-edged sword: While these strategies may signal candidates’ electoral strength, they may also entail reputational costs. In normal times, street campaigns are a non-stigmatized electoral practice. During the Covid-19 pandemic, however, they imposed health risks. Employing data from a national survey experiment conducted in Brazil prior to the 2020 municipal elections (N = 2025), we extend research on the employment of stigmatized campaigns and the gendered dynamics of electoral viability. We find that voters evaluate candidates who engage in face-to-face activities as less electorally viable and report lower intent to support them. These dynamics do not impact all candidates equally: Voters more harshly punish women candidates who conduct street campaigns than men, leading women to lose the advantage they have over men when both employ non-stigmatized campaign practices.